Pengaruh Media Gambar terhadap Kemampuan Menyusun Kalimat Siswa Kelas II Sekolah Dasar Negeri Haurgeuliskolot Indramayu - Dini Ashari; Moch. Hasyim Fanirin; Kartini, Kartini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study discusses the effect of media images on the ability to compose sentences for second grade students at Haurgeuliskolot Indramayu Public Elementary School. As for the background of conducting this research, the researcher felt that grade II students had difficulty arranging jumbled sentences into correct sentences. The purpose of this study was to determine the effect of the use of media images on the ability to compose sentences for class II students of Haurgeuliskolot Indramayu Public Elementary School. This type of research uses quantitative methods by way of descriptive statistical analysis through a one group pretest-posttest design. The subjects in this study were 20 students of grade II SD Negeri Haurgeuliskolot Indramayu and were given two tests, namely the initial test (Pretest) and the final test (Posttest). Data analysis used is descriptive statistics in the form of validity tests, reliability tests, and normality tests, to determine the value of the Paired Sample T test. The results of this study showed that 20 students were given 2 pretest and posttest questions. Based on the results of the Paired Sample T test between picture media and the ability to compose random sentences, the T count 9.11 is greater than the T table 2.092, at a significant level of 0.05 (a = 5%). This figure shows that the calculated T value is greater than the table T value in the T test distribution list at a 0.05 with db=20-1, it can be said that H0 is rejected and H1 is accepted. This means that there is an influence in the use of media images on the ability to compose random sentences for students.